Metode Dakwah Digital pada Instagram @syiarbudayaislam dalam Mempromosikan Budaya Islam - Rahmat Herman Simabur; Asep Ahmad Siddiq; Ahmad Mudakir (Jurnal Riset Komunikasi Penyiaran Islam, 2025)
Abstract. This study aims to determine the da'wah method used by the Instagram account @syiarbudayaislam in promoting Islamic culture to the digital community. In the era of social media, da'wah through platforms such as Instagram has become an effective strategy for conveying Islamic messages. This study uses a descriptive qualitative approach with a content analysis method. The theory used refers to the da'wah method according to Samsul Munir Amin, namely bil lisan (verbal), bil qalam (written), and bil hal (behavior/exemplary). The results show that the @syiarbudayaislam account consistently conveys da'wah messages through creative and educational content by utilizing Instagram features such as feeds, reels, and stories. Islamic messages are packaged in the form of stories about culture, traditions, art, and Islamic historical figures in Indonesia. The approach used is persuasive, communicative, and adapted to the characteristics of the younger generation. The use of visual symbols and positive narratives also strengthens the delivery of da'wah. Abstrak. Artikel bertujuan mengetahui metode dakwah yang digunakan oleh akun Instagram @syiarbudayaislam dalam mempromosikan budaya Islam kepada masyarakat digital. Di era media sosial, dakwah melalui platform seperti Instagram menjadi strategi efektif untuk menyampaikan pesan keislaman. Artikel menggunakan pendekatan kualitatif deskriptif dengan metode analisis isi konten. Teori yang digunakan mengacu pada metode dakwah menurut Samsul Munir Amin, yaitu bil lisan (verbal), bil qalam (tertulis), dan bil hal (perilaku/keteladanan). Hasil penelitian menunjukkan bahwa akun @syiarbudayaislam secara konsisten menyampaikan pesan dakwah melalui konten kreatif dan edukatif dengan memanfaatkan fitur Instagram seperti feed, reels, dan story. Pesan keislaman dikemas dalam bentuk cerita budaya, tradisi, seni, serta tokoh-tokoh sejarah Islam di Indonesia. Pendekatan yang digunakan bersifat persuasif, komunikatif, dan disesuaikan dengan karakteristik generasi muda. Penggunaan simbol visual dan narasi positif turut memperkuat penyampaian dakwah.